Rethinking the Historiography of the Spanish Civil War: Multifarious approaches to a contested past (2022)
This paper aims to delve into the underlying trends of the contemporary historiography of the Spanish Civil War (1936-1939). Under the guidance of historical accounts developed outside Spain before the end of the Francoist dictatorship (1939-1977), and during the transition to democracy (1977-1983), some Spanish historians strove to write a bias-free and fact-based depiction of the war and its aftermath. By relying on closereadings of historical documents, those historians assumed their methodology to be the most accurate when dealing with historical events that are so contested. However, recent shifts in the way this past has been remembered in Spain haveproduced a historiography endorsing new perspectives, which has also given rise to controversies among historians regarding the scope of and the assumptions underlying their work. To understand the currents of these debates, this paper echoes these groundbreaking approaches and attempts to illuminate how the influence of the social movement of «historical memory» has led Spanish historians to question their assumptions and endorse a more heterodox and interdisciplinary approach to engaging with the history of the Spanish Civil War.